Microwave-Assisted Oxidation of Alcohols Using Zinc Polyoxometalate - Kasprzyk, Wiktor; Galica, Mateusz; Bednarz, Szczepan; Bogdał, Dariusz (Synlett, 2014)
In the presence of 30% aqueous hydrogen peroxide and [WZn3(H2O)2][ZnW9O34)2]12– polyoxometalate as a catalyst, primary and secondary alcohols were oxidized to carboxylic acids and ketones, respectively, in short reaction times (ca. 15 min) under microwave-pressurized conditions.
Keywords: oxidation; hydrogen peroxide; catalysis; alcohols; microwave irradiation